The Effectiveness of Transdiagnostic Treatment on Mental Fatigue, Stress Coping Style and Hypochondriasis in Women - Hanieh Miri; Parviz Karimi Sani (Iranian Journal of Educational Research)
Objective : The objective of this investigation was to examine the efficacy of transdiagnostic therapy in alleviating psychological distress, stress coping strategies, and Hypochondriasis among women. Methods: This study followed a semi-experimental design, focusing on practical applications, and employed a pre-test, post-test design with a control group for data collection. The sample size was determined to be 384 individuals using Morgan's formula, from which 30 married women were selected and divided into two groups of 15 for both the experimental and control groups. The research employed Chalder's fatigue questionnaire (1993), Andrew Parker's stress coping style questionnaire (1990), and Evans' hypochondria questionnaire (1980) as the data collection instruments. The intervention consisted of ten training sessions over two and a half months, with each session lasting 90 minutes and occurring once a week. Analysis of covariance was conducted using SPSS version 18 software to test the hypotheses. Results: The findings of the data analysis indicated that transdiagnostic therapy has a significant impact on mental fatigue among women. Furthermore, transdiagnostic treatment also influences women's stress coping style and hypochondriasis. Conclusions: The discoveries may yield practical implications that are beneficial to practitioners and scholars specializing in stress and anxiety within the field of therapy and counselling.